Kinome profiling of osteoblasts on hydroxyapatite opens new avenues on biomaterial cell signaling. Issue 9 (11th June 2014) - Gemini‐Piperni, Sara; Milani, Renato; Bertazzo, Sérgio; Peppelenbosch, Maikel; Takamori, Esther R.; Granjeiro, José Mauro; Ferreira, Carmen V.; Teti, Anna; Zambuzzi, Willian
ABSTRACT In degenerative diseases or lesions, bone tissue replacement and regeneration are important clinical goals. The most used bone substitutes today are hydroxyapatite (HA) scaffolds. These scaffolds, developed over the last few decades, present high porosity and good osteointegration, but haven't completely solved issues related to bone defects. Moreover, the exact intracellular mechanisms involved in the response to HA have yet to be addressed. This prompted us to investigate the protein networks responsible for signal transduction during early osteoblast adhesion on synthetic HA scaffolds. By performing a global kinase activity assay, we showed that there is a specific molecular machinery responding to HA contact, immediately triggering pathways leading to cytoskeleton rearrangement due to activation of Adducin 1 (ADD1), protein kinase A (PKA), protein kinase C (PKC), and vascular endothelial growth factor (VEGF). Moreover, we found a significantly increased phosphorylation of the activating site Ser‐421 in histone deacetylase 1 (HDAC1), a substrate of Cyclin‐Dependent Kinase 5 (CDK5). These phosphorylation events are hallmarks of osteoblast differentiation, pointing to HA surfaces ability to promote differentiation. We also found that AKT was kept active, suggesting the maintenance of survival pathways. Interestingly, though, the substrate sequence of CDK5 also presented higher phosphorylation levels when compared to control conditions. To our knowledge, this kinase has never before been related to osteoblast biology, opening a new avenue of investigation for novel pathways involved in this matter. These results suggest that HA triggers a specific intracellular signal transduction cascade during early osteoblast adhesion, activating proteins involved with cytoskeleton rearrangement, and induction of osteoblast differentiation. Biotechnol. Bioeng. 2014;111: 1900–1905. © 2014 Wiley Periodicals, Inc.